Penerapan Sense of Place sebagai Upaya Konservasi Kawasan : Studi Kasus pada Kampung Arab Pasar Kliwon - Najmi Muhamad Bazher; Kusumaningdyah Nurul Handayani; Tri Yuni Iswati (Universitas Sebelas Maret Surakarta, 2017)
Urban conservation plays a siginificant part in urban design to develop historical quarter, in which sense of place theory can be applied. Kampung Arab Pasar Kliwon, an ethnic cultural quarter in Surakarta, is the case of this urban conservation study. It’s chosen due to the city goverment’s neglect on the development of the heritage area. The conservation includes living heritages in the area, which allows the place to be designated as living museum. This study rises a question on the concept of Kampung Arab Pasar Kliwon conservation, using sense of place theory, on desigining living museum. Answer to the stated issue is enhancing the activity, physical setting, and image in urban area and heritage buildings. Research method used in this study is qualitative-study case. On the street, sense of place is utilised to enhance economic activity, street life activity, cultural activity, and educational activity through urban physical element. In the heritage building, sense of place acts to preserve existing activities and develop or add new activities, room atmosphere, and building exterior. The built physical elements, accommodating the existing and new activities, are designed to conjure particular images (legibility, knowledgibility, and psychological access) through conservation actions (preservation, reconstruction, and infill).